PENGARUH MERCHANDISING, ATMOSFIR TOKO DAN PROMOSI TERHADAP IMPULSE BUYING (STUDI PADA PELANGGAN ALFA-MART DI DENPASAR) - Ni Putu Ayu Lindasari; Anak Agung Putu Agung; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
In the current era where business competition is getting tighter, it makes all business players think harder to find ways to survive or even win business competition. Technological advances also affect the ways or strategies of business people in formulating marketing efforts or marketing efforts to attract or influence consumer spending interests, especially impulse buying. The population of this research is Alfa-mart customers in Denpasar City. The sampling technique used a purposive sampling method. The data analysis technique used to test the deep hypothesis is multiple linear regression analysis. The results showed that merchandising, store atmosphere and promotions have a positive and significant effect on impulse buying. Further researchers are expected to add variables other than merchandising, shop atmosphere and promotions, because there are still other factors that can influence impulse buying.